Implementation of Intrusion Detection System With Suricata on Ubuntu 22.04 LTS - Wahyat, Wahyat; Kudadiri, Parlindungan (Jurnal Teknologi Elekterika, 2024)
This study seeks to put into action and assess the effectiveness of a Suricata based Intrusion Detection System (IDS), on a Linux Ubuntu 22 04 operating system setup. Suricata was selected as the IDS for its features and strong performance, in identifying types of cyber threats. The execution procedure involves setting up Suricata through installation configuring it and conducting tests in a controlled setting. The efficiency assessment entails studying the detection accuracy alarm rate and response time of Suricata when confronted with attack scenarios. The findings, from the research are anticipated to enhance the protection of information systems that operate using Linux as their base platform.